A cross-cultural analysis of the speech act of congratulating in Kabyle and Jordanian Arabic. (2021) - Alghazo, Sharif; Zemmour, Sabrina; Al Salem, Mohd Nour; Alrashdan, Imran
Abstract: Congratulating others is an essential aspect of human social interaction and a speech act that is realised differently in languages. This study aims to investigate the pragmalinguistic realisations of the speech act of congratulating in Kabyle and Jordanian Arabic (JA) by comparing the strategies that Kabyle-speaking and JA-speaking students employ when offering congratulations. The data are analysed with reference to social status, gender and cultural background of the participants. A Discourse Completion Test (DCT) which included four situations of different social statuses is used to collect data from 30 JA-speaking students (15 males and 15 females) at the University of Jordan and 30 Kabyle-speaking students (15 males and 15 females) from three different universities in Algeria region of Kabylie. Elwood's (2004) framework is adopted in the classification of strategies. A mixed-method approach is applied in the analysis with the frequency of strategies being quantitatively analysed and the semantic formulas vis-à-vis status are qualitatively analysed. The results show that there are slight differences in the use of congratulating strategies between the two groups of participants, and these are discussed in terms of sociopragmatic and sociocultural dimensions of variational pragmatics.